006.89 METHODOLOGICAL PROCESSING OF QUALITY CONTROL OF TECHNOLOGICAL PROCESSES OF MANUFACTURING ENTERPRISES - Xolboyeva, Shoxsanam; Kosimov, Ahtam (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
In this article, the creation of a market-oriented quality management system, the development of the internal and external environment of the market-oriented quality management system, the tolerance system for the change of the actual values of quality indicators during the production process without significantly affecting the technical level of quality regulation of possible limits, a comprehensive standardization system is about defining the program and regulating all processes of quality management.